Pengaruh Modal Usaha Dan Karakteristik Pelaku Usaha Terhadap Perkembangan UMK Di Desa Laubaleng Kecamatan Laubaleng Kabupaten Karo - Malango, Sintia Miramis Novita Mala Br; Siahaan, Audrey M.; Hutapea, Herti Diana (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to find out how business capital and business characteristics influence the development of MSEs in Laubaleng Village, Laubaleng District, Karo Regency. To find out the influence of business capital and characteristics of business actors on the development of MSEs in Laubaleng Village, Laubaleng District, Karo Regency. The type of research used is quantitative research. Quantitative research can be interpreted as a research method based on the philosophy of positivism, used for research on certain populations or samples, sampling techniques are usually carried out randomly, use of data, using research instruments, quantitative statistical data analysis with the aim of testing hypotheses that have been established. set. The research results show that business capital (X1) has a positive and significant effect on the development of MSEs in Laubaleng village, Laubaleng sub-district, Karo district. This is shown by the significance value of the resulting business capital variable being 0.000, which is smaller than the significance level of 0.05. This is in line with several previous research results which show that there is a significant influence of business capital on business development. Based on the results of the analysis carried out, the business capital variable (X1) partially influences the development of MSEs (Y) with a value of tcount ttable. Thus, the business actor variable has a significant influence on the development of MSEs in Laubaleng Village, Laubaleng District, Karo Regency.